2015
DOI: 10.1159/000437150
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Intracranial Haemorrhages Associated with Vitamin K Antagonist Oral Anticoagulants in Spain: TAC Registry

Abstract: Background: Vitamin K antagonist oral anticoagulants (VKA-OACs) are effective for primary and secondary prevention of embolic events. The rate of haemorrhagic neurological complications in patients admitted to neurology departments in Spain is not yet known. Aims: We aimed to determine the clinical and epidemiological characteristics of patients with intracranial haemorrhage secondary to VKA-OACs as well as the incidence of this severe complication. Methods: We conducted a retrospective, descriptive, multi-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…A Spanish retrospective analysis from 2014 reported a very similar 40% mortality rate and a favorable outcome in only 25% of all patients [15]. A recent German prospective, multicenter, observational study of nontraumatic NOAC-related ICH reported a 28% mortality rate and a favorable outcome in 25% of the patients [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Spanish retrospective analysis from 2014 reported a very similar 40% mortality rate and a favorable outcome in only 25% of all patients [15]. A recent German prospective, multicenter, observational study of nontraumatic NOAC-related ICH reported a 28% mortality rate and a favorable outcome in 25% of the patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported a mortality rate of 52-67% [14]. With time, the results improved and the described mortality rate was 28-40%, whereas a favorable outcome was observed in 10-35% [15,16,17]. In a recent study, the outcome appeared to be similar to that of VKA-related ICH [17].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of intracranial hemorrhage (ICH) in patients receiving VKAs is 0.3-3%, i.e., an 8-to 10-fold greater risk than in patients who do not take VKAs [3,4]. Furthermore, not only is the risk of ICH increased, but once the hemorrhage occurs, the initial volume [5], risk of expansion, severity, and probability of death are also higher [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, not only is the risk of ICH increased, but once the hemorrhage occurs, the initial volume [5], risk of expansion, severity, and probability of death are also higher [6,7]. The mortality rate of ICH is 40-67% [3,4,6], and the probability of functional recovery is 17-24.3% [3].…”
Section: Introductionmentioning
confidence: 99%
“…According to beliefs one of the most serious internal hemorrhage is the cerebral haemorrhage which is one (but less common) form of stroke [1]. Bleedings are known side effects of vitamin K antagonist therapy that is often used to prevent obstructive (ischemic) stroke [2]. Vitamin K deficiency bleeding (VKDB) was first realized as hemorrhagic disease of newborns, but today more cases are to be seen in connection with vitamin K antagonist therapy in the elderly.…”
Section: Introductionmentioning
confidence: 99%